Nineteenth-Century Jewish Literature : a Reader. - Hess, Jonathan M., 1965-2018 (Stanford Studies in Jewish History and C., 2013)
Recent scholarship has brought to light the existence of a dynamic world of specifically Jewish forms of literature in the nineteenth century-fiction by Jews, about Jews, and often designed largely for Jews. This volume makes this material accessible to English speakers for the first time, offering a selection of Jewish fiction from France, Great Britain, and the German-speaking world. The stories are remarkably varied, ranging from historical fiction to sentimental romance, to social satire, but they all engage with key dilemmas including assimilation, national allegiance, and the posit.